Yeast diversity related with Touriga Nacional Grape variety - Duarte, Filomena (2011)
The diversity of yeast species related with the grape variety Touriga Nacional was evaluated at four distinct vineyards of three Portuguese wine regions. Samples were collected 48 h after crushing, and when the loss of CO2 reached 70 g/L. Restriction profiles analysis of 26S rDNA region with the endonucleases HaeIII, CfoI, HinfI, ApaI and MseI was used to characterize the five hundred and nine isolates obtained. A total of twenty yeast species were found. As expected higher species diversity was obtained for the initial sampling time. The most representative species was Hanseniaspora uvarum, which was detected in grape must from all the vineyards, followed by Candida zemplinina. Some species like Pichia membranifaciens, Pichia kluyveri var kluyveri, Candida railenensis, Saccharomycopsis vini, Candida diversa, among others, were only detected in grape must from one vineyard. None of the isolates belonged to the species Saccharomyces cerevisiae.